Impact of Workplace Bullying on Employee Intentions to Leave and Mediating Role of Employee Engagement: Banking Sector of Pakistan - Salman, Shahrukh; Chawla, Rahil Nazar; Naz, Muqaddas; Khan, Rana Muhammad Naeem (Pakistan Journal of Humanities and Social Sciences, 2023)
Employee intentions to leave may entail expensive consequences for the organization. This study examined the mediating impact of employee engagement on the relationship between workplace bullying and employee intentions to leave. This study adopts a quantitative approach to find the relationship between variables. The data was collected from the banking sector of Pakistan through a random sampling technique using a self-administered questionnaire where 350 was the sample. Structural equation modeling (SEM) analysis showed that employee engagement substantially mediates the relationship between workplace bullying and the intention to leave the organization. However, workplace bullying and the intention to leave the organization are positively associated. The results were integrated from a conservation of resources perspective and recommendations for practice were made.